2004
DOI: 10.1103/physreva.69.012711
|View full text |Cite
|
Sign up to set email alerts
|

Isotope-selective photoionization for calcium ion trapping

Abstract: We present studies of resonance-enhanced photoionization for isotope-selective loading of Ca ϩ into a Paul trap. The 4s 2 1 S 0 ↔4s4p 1 P 1 transition of neutral calcium is driven by a 423 nm laser and the atoms are photoionized by a second laser at 389 nm. Isotope selectivity is achieved by using crossed atomic and laser beams to reduce the Doppler width significantly below the isotope shifts in the 423 nm transition. The loading rate of ions into the trap is studied under a range of experimental parameters f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
138
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 29 publications
0
138
1
Order By: Relevance
“…It was observed that even if the 390nm laser is operated below its lasing threshold current, its weak incoherent emission was sufficient to load ions [4]. The efficiency of this process was observed to be independent of the linewidth, as a result of the broad autoionizing resonances in the vicinity of the first ionization limit [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was observed that even if the 390nm laser is operated below its lasing threshold current, its weak incoherent emission was sufficient to load ions [4]. The efficiency of this process was observed to be independent of the linewidth, as a result of the broad autoionizing resonances in the vicinity of the first ionization limit [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The S-P dipole transition has the broadest linewidth of all transitions in Ca I (35.4MHz) and can easily be saturated with a laser tuned to resonance [4]. To excite the electron from the 1 P 1 -state into the continuum above the first ionization limit, a second photon of wavelength λ ≤ 389.89nm is necessary, as e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations